Undergraduate nursing students' education and training in aseptic technique: A mixed methods systematic review. (14th July 2021) - Hawker, Clare; Gould, Dinah; Courtenay, Molly; Edwards, Deborah
Abstract: Aim: To appraise and synthesize empirical studies exploring undergraduate nursing students' education and training in aseptic technique. Design: Mixed methods, systematic literature review adopting Joanna Briggs Institute methodology. Data sources: Thirteen electronic databases were searched 1996–2020, followed by searches with a general browser, hand‐searching key journals and reviewing reference lists of retrieved papers. Review methods: Potentially eligible papers were scrutinised by two reviewers. Those eligible were critically appraised and quality assessed using the Critical Appraisal Skills Programme and Specialist Unit for Review Evidence checklists. Results: Of 538 potentially eligible studies, 27 met the inclusion criteria. There was limited evidence of the effectiveness of different teaching methods. Students' knowledge, understanding and competency varied and were often poor, although they reported confidence in their ability to perform aseptic technique. Students and qualified nurses perceived that education and training in aseptic techniques might be improved. Conclusion: Education and training in aseptic technique might be improved but the review findings should be viewed cautiously because the studies lacked methodological rigour. Impact: This appears to be the first systematic review to explore undergraduate nursing students' education and training in relation to aseptic technique. There was limited evidence to support the effectiveness of different teaching methods and scope for improving nursing students' knowledge, understanding and competency in aseptic technique. Students and qualified nurses suggested that education and training might be enhanced. More robust studies are required to support education, practice and policy.